Acute scaphoid fractures: making decisions for treating a troublesome bone. (January 2022) - Dias, Joseph J.; Ring, David; Grewal, Ruby; Clementson, Martin; Buijze, Geert Alexander; Ho, Pak-Cheong
Seven aspects of the management of acute scaphoid fractures are open to debate: Diagnosis of true fractures among suspected fractures, assessment of fracture displacement, cast immobilization strategies, the role of surgical fixation, proximal pole fractures, assessment of union, and the underlying objective of treatment. We reviewed current evidence, and our varied interpretations of it, to highlight areas of uncertainty where more evidence might be helpful.